POW'WOW virtual laboratory for wind power forecasting - ViLab. - Kariniotakis,G; Pinson,P; Marti,I; Lozano,S; Giebel,G (2007)
As development and operational use of forecasting solutions take more and more importance in the wind energy sector, the consortium of the European Coordination Action 'Prediction of Wakes, Waves and Offshore Wind' (Pow'Wow) has taken the initiative of setting up a Virtual Laboratory (ViLab). The related objectives are to stimulate research efforts in this field, to tighten the collaboration between forecasters and forecast users, as well as to follow and communicate the state of the art in short term prediction of wind generation. The present note clarifies the benefits for the participants to the ViLab. Also, it describes the methodology employed and some practical issues related to eg. data and confidentiality.